A lightweight and trusted communication protocol for IoT - Junfeng MA; Zhiruo LIU; Guanwen LI; Fei YANG; Juanna DANG (Dianxin kexue, 2021)
With the era of the internet of things (IoT), the protocol stack conversion scheme based on the application-layer’s gateway has problems such as poor performance and end to end security that can’t be guaranteed.A lightweight and trusted IoT IP communication protocol was proposed, which was the main research direction of Protocol and Interface Group in Network 5.0 Industry and Technology Innovation Alliance, the deployment costs of protocol conversion gateways was decreased, the computing and storage overhead of IoT devices was reduced, and end to end communication security was ensured.